2014
DOI: 10.1111/bcpt.12348
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of miR‐21 and miR‐23a Contributes to As2O3‐induced hERG Channel Deficiency

Abstract: Arsenic trioxide (As 2 O 3 ) is used to treat acute pro-myelocytic leukaemia. However, the cardiotoxicity of long QT syndrome restricts its clinical application. Previous studies showed that As 2 O 3 can damage the hERG current via disturbing its trafficking to cellular membrane. Consistent with these findings, in this study, we reported that As 2 O 3 inhibited hERG channel at both protein and mRNA levels and damaged hERG current but did not affect channel kinetics. Further, we demonstrated that As 2 O 3 up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…These gene products play vital roles in many physiological processes, in tissue repair and anti‐inflammatory responses. It has been confirmed that Sp1 is a direct target of miR‐21 in human smooth muscle cells and HEK293 cell lines . These findings collectively suggest that Sp1 may be a candidate target gene of miR‐21 in mouse cells.…”
Section: Discussionmentioning
confidence: 99%
“…These gene products play vital roles in many physiological processes, in tissue repair and anti‐inflammatory responses. It has been confirmed that Sp1 is a direct target of miR‐21 in human smooth muscle cells and HEK293 cell lines . These findings collectively suggest that Sp1 may be a candidate target gene of miR‐21 in mouse cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its remarkable effects on certain cancer types, ATO has adverse effects, such as cardiac toxicity; thus, its clinical applications are restricted [24-26]. ATO cardiotoxicity is known to proceed by As 3+ binding to sulfhydryl groups of proteins, thereby damaging the mitochondrial respiratory chain and generating excessive ROS, eventually leading to myocardial cell apoptosis [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic use of ATO is burdened by broad cardiotoxicity that is characterized by a prolonged QT interval, which can result in life-threatening torsade de pointes and cardiac death. Substantial evidence has been collected demonstrating that ATO can disrupt the HERG current by interfering with trafficking to the cellular membrane, as well as through reduction in HERG protein abundance [ 6 ]. A previous analysis of ATO-induced long QT syndrome revealed that ATO treatment of guinea pigs caused an increase in transforming growth factor β1 (TGF-β1) secretion, while HERG protein expression was decreased [ 7 ].…”
Section: Introductionmentioning
confidence: 99%